Collective access to justice : assessing the potential of class actions in England and Wales / Michael Molavi. - Molavi, Michael (Bristol shorts research., 2021)
At a time when the collective redress landscape is undergoing a period of transformative change, this important and timely research focuses on class actions in England and Wales. Aiming to promote access to justice, this pioneering work separates fact from fiction in an easily digestible way, offering progressive solutions for reform.